DOI: 10.32657/10356/42302
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and analytical studies on the seismic behavior of reinforced concrete columns with light transverse reinforcement

Abstract: Structures made up of reinforced concrete columns with light transverse reinforcement are very common in a region of low to moderate seismicity, and are the predominant structural system in Singapore. Recent post-earthquake investigations have indicated that extensive damage in reinforced concrete columns with light transverse reinforcement occurs due to excessive shear deformation that subsequently leads to shear failure, axial failure and eventually full collapse of the structures. Therefore, a thorough eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Post-earthquake reconnaissance surveys indicate that the reinforced concrete (RC) columns of old buildings are often vulnerable to shear failure during earthquakes. Based on previous studies (Matsukawa, 2013; Nakamura and Yoshimura, 2002; Ousalem, 2006; Tran, 2010; Uchida and Uezono, 2003), the consensus is that shear failure can deteriorate both the horizontal and axial capacities of RC columns. If the axial load of a shear-damaged RC column with a significantly deteriorated axial capacity cannot be distributed to the neighboring columns by the surrounding beams and slabs, axial collapse may occur.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-earthquake reconnaissance surveys indicate that the reinforced concrete (RC) columns of old buildings are often vulnerable to shear failure during earthquakes. Based on previous studies (Matsukawa, 2013; Nakamura and Yoshimura, 2002; Ousalem, 2006; Tran, 2010; Uchida and Uezono, 2003), the consensus is that shear failure can deteriorate both the horizontal and axial capacities of RC columns. If the axial load of a shear-damaged RC column with a significantly deteriorated axial capacity cannot be distributed to the neighboring columns by the surrounding beams and slabs, axial collapse may occur.…”
Section: Introductionmentioning
confidence: 99%
“…For RC buildings with earthquake-induced damage, several evaluation models have been proposed based on theory or experimental analysis to estimate the residual axial capacities of shear-damaged columns. These evaluation models can be divided into the following three types: (1) theoretical models (Elwood and Moehle, 2005; Matsukawa, 2013; Ousalem, 2006; Tran, 2010; Uchida and Uezono, 2003); (2) semi-empirical models (Kato et al, 2008; Nakamura and Yoshimura, 2002); and (3) empirical models (Japan Building Disaster Prevention Association (JBDPA), 2005). However, the residual axial capacities of RC frames have not yet been sufficiently studied, and the related previous studies are very limited (Elwood and Moehle, 2008; Ghannoum and Moehle, 2012; Murray and Sasani, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, several evaluation models have been proposed to evaluate the residual axial capacities of the columns. These models can be divided into three types: (1) theoretical models (Elwood and Moehle, 2005; Matsukawa, 2013; Ousalem, 2006; Tran, 2010; Uchida and Uezono, 2003); (2) semi-empirical models (Kato et al, 2008; Nakamura and Yoshimura, 2002) and (3) empirical models (Japan Building Disaster Prevention Association (JBDPA), 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Compar. ing with the case of columns with deformed rebars in Tran's tests (2010i19 ) and Tran and Li ' s tests,< 34 ) strain at different locations of longitudinal rebars in the column with plain rebars did not vary significantly as in columns with deformed rebars.…”
mentioning
confidence: 73%
“…Five specimens in this study were designed to be similar to columns with deformed rebars in Tran ' s tests< 19 ) The comparisons also showed that for short columns (all specimens with shear span to depth ratios of 1.7) deformed reinforcement did not produce higher initial stiffness. The reason was because the flexural cracks occurred in columns with deformed rebars reducing its initial stiffness gradually.…”
Section: Comparisons With Columns Having Deformed Rebarsmentioning
confidence: 87%